Analysis of risk factors for prostate cancer patients. (2015) - Alqahtani, Khaled S.; Srinivasan, Shankar; Mital, Dinesh P.; Haque, Syed
This study tries to identify some of the key risk factors for those patients who are more likely to be diagnosed with prostate cancer. These risk factors include age, race/ethnicity, family history of prostate cancer, family history of any other type of cancer, obesity, smoking, alcohol abuse, cholesterol, vitamin D deficiency, inflammation of prostate, vasectomy, and hypertension. The study finds, age, race, positive family history of prostate cancer, a positive family history of any other type of cancer, hypercholesterolemia, vitamin D deficiency, inflammation of prostate, vasectomy, and hypertension are significantly associated with prostate cancer. However, obesity, alcohol abuse, and smoking show negative association with prostate cancer.